Facing Malaria Parasite with Mosquito Symbionts - Favia, Guido; Ricci, Irene; Scuppa, Patrizia; Damiani, Claudia; Rossi, Paolo; Capone, Aida; Freece, Chenoa De; Valzano, Matteo; Cappelli, Alessia; Mosca, Michela; Ulissi, Ulisse (IntechOpen, 2012)
None